2017
DOI: 10.1177/0890117117694450
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Worksite Intervention for Male Construction Workers on Dietary and Physical Activity Behaviors, Body Mass Index, and Health Outcomes: Results of a Randomized Controlled Trial

Abstract: Intervention participants showed positive changes in vigorous PA and intake of sugar-sweetened beverages compared to controls, as well as effects on weight-related outcomes at 6 months. Long-term effects were still promising but not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 54 publications
4
101
0
Order By: Relevance
“…Following title/abstract screening, 284 references remained from which an additional 258 articles were further removed following a full text review. Ultimately, 26 peer-reviewed journal articles (figure 1), representing 24 studies and independent samples,43–68 were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following title/abstract screening, 284 references remained from which an additional 258 articles were further removed following a full text review. Ultimately, 26 peer-reviewed journal articles (figure 1), representing 24 studies and independent samples,43–68 were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies45 47 48 50 51 53 56 59 60 66–68 reported an additional follow-up measure at least 12 months postintervention (figure 3). The overall mean effect for long-term physical activity change was small but significant ( d =0.32; SE=0.09; 95% CI 0.15 to 0.48; p<0.001) and had a significant heterogeneous distribution (Q w =55.81, p<0.001; I 2 =80.29).…”
Section: Resultsmentioning
confidence: 99%
“…Results reported include a drop in LDL cholesterol, 9,10 total cholesterol, 10,11 and LDL particle size. 9,12 Reductions in body weight or body mass index (BMI) 11,13 and blood pressure 10,13 were also reported. Behavioral changes were assessed in 2/5 studies, with one study finding a significant increase in physical activity, 11 whereas another saw no changes in physical activity.…”
Section: Cholesterolmentioning
confidence: 99%
“…Behavioral changes were assessed in 2/5 studies, with one study finding a significant increase in physical activity, 11 whereas another saw no changes in physical activity. 13 For dietary outcomes, one study 11 reported increased fruit and vegetable consumption, whereas another study reported reduced sugar-sweetened beverage consumption at an early follow-up; but this reduction was not sustained at any other follow-up time points. 13 In summary, the cholesterol-related studies included in the 2019 Addendum to the HWC Compendium used mostly RCTs with either positive or null findings regarding primary study outcomes.…”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation